Particle-Assisted Dermal Penetration-A Simple Formulation Strategy to Foster the Dermal Penetration Efficacy - Sabrina Wiemann; Cornelia M. Keck (MDPI AG, 2022)
(1) Background: The study systematically investigated the influence of dispersed particles within a topical formulation on the dermal penetration efficacy of active compounds that are dissolved in the water phase of this formulation. The aim was to prove or disprove if particle-assisted dermal penetration can be used for improved dermal drug delivery. (2) Methods: Fluorescein was used as a surrogate for a hydrophilic active ingredient (AI). It was dissolved in the water phase of different formulations with and without particles. Two different types of particles (titanium dioxide and nanostructured lipid carriers (NLC)) were used. The influence of particle size and number of particles and the influence of skin hydrating excipients was also investigated. (3) Results demonstrate that the addition of particles can strongly increase the dermal penetration efficacy of AI. The effect depends on the size of the particles and the number of particles in the formulation, where smaller sizes and higher numbers resulted in higher penetration parameters. Formulations with NLC that contained 20% w/w or 40% w/w particles resulted in an about 2-fold higher amount of penetrated AI and increased the penetration depth about 2.5-fold. The penetration-enhancing effect was highly significant (p < 0.001) and allowed for an efficient delivery of the AI in the viable dermis. In contrast, the penetration-enhancing effect of excipients that increase the skin hydration was found to be very limited and not significant (≤5%, p > 0.05). (4) Conclusions: Based on the results, it can be concluded that particle-assisted dermal penetration can be considered to be a simple but highly efficient and industrially feasible formulation principle for improved and tailor-made dermal drug delivery of active compounds.